2020
DOI: 10.3390/pr8121639
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Organic Pollutants onto Soils: Surface Diffusion Mechanism of Congo Red Azo Dye

Abstract: For the protection of human and ecological receptors from the effects of soil pollution with chemical compounds, we need to know the behavior and transport of pollutants in soil. This work investigated the Congo red (CR) acid dye sorption on three natural soils collected from central and northeastern regions of Romania, symbolized as IS-65, IS-T, and MH-13. To define the mechanism of sorption and identify the rate governing step, various diffusion models such as Weber–Morris intraparticle diffusion, Boyd, film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…While the steeply rising first part defines initial rapid absorption by boundary layer effects, the plateau-like second part, which is associated with intraparticle diffusion, takes place after completion of outer surface coverage by the first process. This multilinearity of the curve suggests that external mass transfer and intraparticle diffusion are involved in different phases of the Tl sorption process on gamma alumina nanoparticles [100][101][102][103]. Senol, Z.M et al (2010) [97] obtained similar results on the elimination of Tl(I) onto polyacryamide-aluminosilicate composites.…”
Section: Intraparticle Diffusion Of Thallium Adsorption By Gamma Nano...mentioning
confidence: 83%
“…While the steeply rising first part defines initial rapid absorption by boundary layer effects, the plateau-like second part, which is associated with intraparticle diffusion, takes place after completion of outer surface coverage by the first process. This multilinearity of the curve suggests that external mass transfer and intraparticle diffusion are involved in different phases of the Tl sorption process on gamma alumina nanoparticles [100][101][102][103]. Senol, Z.M et al (2010) [97] obtained similar results on the elimination of Tl(I) onto polyacryamide-aluminosilicate composites.…”
Section: Intraparticle Diffusion Of Thallium Adsorption By Gamma Nano...mentioning
confidence: 83%
“…CAC has a larger Kid value than NBC, indicating that its outer film diffusivity is more dominant. Betianu et al [21] found that high Kid values were associated with high initial turbidity concentrations and the well-known boundary layer effect. This conclusion was substantiated by the findings (table 3), which demonstrated that the boundary layer surrounding CAC was thicker than that surrounding NBC.…”
Section: Resultsmentioning
confidence: 99%
“…Since the slowest reaction rate is considered the rate‐limiting step, is it worth noting that Region 3 ( k 3 ), which corresponds to CO 2 diffusion into the micropore region, is the rate‐limiting process. Smaranda Bețianu et al 33 . suggested that the intra‐particle diffusion as the rate‐limiting step points to the high intensity of external transport.…”
Section: Resultsmentioning
confidence: 99%